(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The research aims to determine the effect of internal resistance on electric current in a closed circuit. The Sample of this study of 20 sample variation.The research method used was the ex post facto method, by not providing treatment but directly conducting related evaluations. Data analysis technique used is by regression analysis. From the results of the analysis it was found that Freghitung= 4.282 and Freg-table = 4.130 (Freg-count > Freg-table), so the conclusion of this study is that there is a very large effect of internal resistance on electric current in a closed circuit.